The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1085/jgp.2021ecc17
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for diamide modulation of ryanodine receptor

Abstract: Diamide insecticides target insect ryanodine receptors (RYRs) and cause dysregulation of calcium signaling in insect muscles and neurons, generating worldwide sales over 2 billion US dollars annually. Several resistance mutations have been reported to reduce the efficacy of the diamides, but the exact binding sites and mechanism of resistance mutations were not clear. Recently, we solved the cryo-electron microscopy (cryo-EM) structure of RYR in complex with the anthranilic diamide chlorantraniliprole (CHL). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…The partial sequencing of the ryanodine receptor genes of H. armigera-resistant strains to flubendiamide showed no mutations in the region that covers the transmembrane regions II to VI. This C-terminal region was formerly described to contain target site mutations [15,47]. The primary lepidopteran resistance mechanism to diamides is the mutation in RyR, which can promote very high resistance ratios [15].…”
Section: Discussionmentioning
confidence: 99%
“…The partial sequencing of the ryanodine receptor genes of H. armigera-resistant strains to flubendiamide showed no mutations in the region that covers the transmembrane regions II to VI. This C-terminal region was formerly described to contain target site mutations [15,47]. The primary lepidopteran resistance mechanism to diamides is the mutation in RyR, which can promote very high resistance ratios [15].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, CaMBD2 and CaMBD3 showed nanomolar a nity to Ca 2+ -CaM in both RyR1 and RyR2 at the high [Ca 2+ ] cyto condition and micromolar a nity to apo-CaM at the low [Ca 2+ ] cyto condition, suggesting that these sites are more likely to be the CaM-binding regions in RyR. Recently, several cryo-EM structures of full-length RyRs in complex with CaM were solved, con rming that CaMBD2 is the genuine CaM-binding domain in both RyR1 and RyR2 (Gong et al, 2019;Ma et al, 2020;Maximciuc et al, 2006). Under low [Ca 2+ ] cyto condition, the C-lobe of apo-CaM binds to the surface of CaMBD2 from the central domain and another -helix from the handle domain, whereas the N-lobe interacts with multiple -helices from the HD1 domain (Gong et al, 2019;Ma et al, 2020;Maximciuc et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The diamide insecticide family, such as ubendiamide (FLU), chlorantraniliprole (CHL), and cyantraniliprole (CYA), can speci cally target a range of agricultural pests, including lepidopteran, hemipteran, and coleopteran pests by activating their RyRs (Cordova et al, 2006;Tohnishi et al, 2005). A recent study by cryo-electron microscopy (EM) revealed that the binding site of diamide insecticide is located at the pseudo voltage-sensor domain (pVSD) in the transmembrane region of RyR (Ma et al, 2020). Interestingly, four mutations associated with diamide-resistance, G4946E, I4790M, Y4701D and Y4922F (diamondback moth numbering), are located exactly at the identi ed diamide binding site and drastically lower their e cacy by hundreds of folds (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations